Heart transplant candidate with medical complexity in the era of prolonged left ventricular assist device support — A case report. Issue 2 (February 2021) - Takada, Takuma; Hattori, Hidetoshi; Kikuchi, Noriko; Ichihara, Yuki; Saito, Satoshi; Endo, Natsumi; Iguchi, Shigekazu; Yoshida, Atsushi; Kikuchi, Ken; Niinami, Hiroshi; Hagiwara, Nobuhisa; Nunoda, Shinichi
Abstract: Heart transplantation improves quality of life and survival in patients with advanced heart failure. However, the shortage of available heart donors and technological advances for left ventricular assist devices (LVAD) have led to longer waiting times for transplantation, and long-term use of LVAD may increase the medical complexity of subsequent transplantation. We present the case of a 35-year-old man who underwent heart transplantation after being supported by an LVAD for 1490 days (∼4 years). He was sensitized with kidney dysfunction and recurrent infections, including candidemia, at the time of transplantation. He underwent a successful heart transplantation with pretransplant plasma exchange, intravenous immunoglobulin administration, early initiation of everolimus, and prompt management of infections. <Learning objective: With a growing number of heart transplant candidates who are supported by left ventricular assist devices for long duration, managing such candidates is becoming increasingly complex and difficult to standardize. The present case had three problems that were linked to each other: (1) anti-HLA antibodies, (2) fungal infection, and (3) pre-transplantation renal dysfunction. Management of heart transplant candidates, including desensitization and immunosuppressive therapies, should be tailored to the individual and the clinical presentation to improve the survival and quality of life.>